EMOTIONAL INTELLIGENCE MODERATED ENTREPRENEURAL SUCCESS (Case Study of SMEs in Semarang City) - Fitrie Arianti; Sarah Destiana (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2023)
Recently, many countries around the world have been experiencing multidimensional crises, including Indonesia, due to the ongoing Covid-19 pandemic. The negative impact has paralyzed the business world, shaken the foundations of the wider community's welfare, and narrowed job opportunities, while the number of people seeking employment continues to increase and unemployment rates keep rising. To address this phenomenon, cultivating an entrepreneurial spirit is considered an appropriate solution.This study aims to analyze the variables that influence the success of entrepreneurship. Several variables suspected of having an impact are Entrepreneurial Characteristics, Competitive Advantage, and Emotional Intelligence as Moderating Variables. Population in this study is micro, small, and medium enterprises (MSMEs) in Semarang city, and the sample consists of 154 respondents obtained through purposive sampling technique. The variables include four factors: Entrepreneurial Characteristics, Competitive Advantage (as Independent Variables), Emotional Intelligence (as Moderating Variables), and Entrepreneurial Success (as Dependent Variable). The data analysis method used hypothesis testing (t-test) and moderated regression analysis (MRA) to test moderating variables.Results show that entrepreneurial characteristics have a significant positive effect on entrepreneurial success, with a significance value of 0.044. Competitive advantage does not have a significant negative effect on entrepreneurial success, with a significance value of 0.131. Meanwhile, emotional intelligence does not function as a moderator between the effect of entrepreneurial characteristics on entrepreneurial success, with a significance value of 0.101, but it can moderate the effect of competitive advantage on entrepreneurial success, with a significance value of 0.041.